2007
DOI: 10.2174/092986607781483912
|View full text |Cite
|
Sign up to set email alerts
|

Ramachandran Plot on The Web (2.0)

Abstract: The Ramachandran plot displays the main chain conformation angles (Phi and Psi) of the polypeptide chain of a protein molecule. The paper reports the updated version of the Ramachandran plot web server and has several improved options for displaying the conformation angles in various regions. In addition, options are provided to display the conformation angles in various secondary structural elements and regions within the user specified Phi and Psi values in the plot. The updated version is accessible at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(85 citation statements)
references
References 12 publications
1
83
0
1
Order By: Relevance
“…One of them (http:// dicsoft1.physics.iisc.ernet.in/rp/) allows numerous possibilities to analyze specific features of the Ramachandran plot (different types of amino acids, sequence-dependent windows, different regions of the map etc. ; Sheik et al, 2002;Gopalakrishnan, Sowmiya et al, 2007). RAMPAGE is another well designed program from the CCP4 software suite (Winn et al, 2011) that can be found at http://mordred.bioc.cam.ac.uk/ rapper/rampage.php, for example.…”
Section: Ramachandran Plots and The Internetmentioning
confidence: 99%
“…One of them (http:// dicsoft1.physics.iisc.ernet.in/rp/) allows numerous possibilities to analyze specific features of the Ramachandran plot (different types of amino acids, sequence-dependent windows, different regions of the map etc. ; Sheik et al, 2002;Gopalakrishnan, Sowmiya et al, 2007). RAMPAGE is another well designed program from the CCP4 software suite (Winn et al, 2011) that can be found at http://mordred.bioc.cam.ac.uk/ rapper/rampage.php, for example.…”
Section: Ramachandran Plots and The Internetmentioning
confidence: 99%
“…32) To validate the modeled structure of Xyn11A, a Ramachandran plot of Xyn11A and template were drawn by the Procheck program. 20) The spot distribution in the Ramachandran plot of the Xyn11A structure was similar to the X-ray structure of the B. circulans xylanase. The results showed that the homology-modeled structure of Xyn11A is reasonable and acceptable.…”
Section: Resultsmentioning
confidence: 53%
“…Validation of the model was carried out using Ramachandran plot calculations computed with the Procheck program. 20) Molecular docking. Xylooligosaccharides preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The result of the amino acid sequence alignment revealed that the H5Sq1 loop has a 50% similarity relative to its template. Then, the geometry and stereochemistry of the loop were validated using Ramachandran plot 2.0 program [23,24]. Of the ten residues of the cleavage loop, nine are located in the fully allowed regions and the other one in the additionally allowed regions of the plot, indicating that the initial structure of the H5Sq1 loop is reasonable.…”
Section: Methodsmentioning
confidence: 99%